PERMAINAN TRADISIONAL DI DESA PASIR PANDAK KECAMATAN KAPUNUHAN KABUPATEN ROKAN HULU - Ilham Arianti; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The traditional game is a kind of game that has been there and continues to be implemented by a next generation of descendants. In the village of Pasir Pandak Kecamtan Kepenuhan Rokan Regency there are jens types of traditional games played by the community of Pasir Pandak Village that is game Gasing, Patok Lele, Kelereng, Bamboo Bamboo or also called Dondobang in this research want to find out about the type of Traditional Games in Pasir Pundak Village. This research is qualitative where the technique of determining Research Subject is Purposive. The Key Informants are Youth Leaders, Customary Leaders and Community Leaders in Pasir Pandak Village.Keywords: Traditional Games